2014
DOI: 10.3892/or.2014.3548
|View full text |Cite
|
Sign up to set email alerts
|

Specific growth inhibition of ErbB2‑expressing human breast cancer cells by genetically modified NK‑92 cells

Abstract: Abstract. The natural killer cell line NK-92 shows great cytotoxicity against various types of cancer. Several types of solid tumor cells, however, can effectively resist NK-mediated lysis by interaction of major histocompatibility complex (MHC) molecules with NK cell inhibitory receptors. To generate a eukaryotic expression vector encoding chimeric antigen receptor scFv anti-erbB2-CD28-ζ and to investigate the expression and action of this chimeric antigen receptor in cancer cells both in vitro and in vivo, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…Furthermore, in CD8 + CTLs isolated from blood samples of breast cancer patients, significant upregulation of FAS [57,58,68] as well as significant downregulation of the T cell receptor (TCR), responsible for antigen recognition and its co-receptor CD28, have been observed [42]. Moreover, numerous studies have shown upregulation in FoxP3 + Tregs [69, 70•, 71] and MDSCs [45,[72][73][74] as well as elevated arginase [75,76], dampening immunity in breast cancer through suppressive actions on CTLs, DCs and NK cells [76,77]. Metabolic enzymes such as indoleamine 2,3-dioxygenase (IDO), which is expressed by tumour cells and MDSCs, can also inhibit immune responses though local depletion of amino acids which are essential for anabolic functions, particularly in T lymphocytes [78,79].…”
Section: Mechanisms Of Immunity Generation and Suppression In Breast mentioning
confidence: 97%
“…Furthermore, in CD8 + CTLs isolated from blood samples of breast cancer patients, significant upregulation of FAS [57,58,68] as well as significant downregulation of the T cell receptor (TCR), responsible for antigen recognition and its co-receptor CD28, have been observed [42]. Moreover, numerous studies have shown upregulation in FoxP3 + Tregs [69, 70•, 71] and MDSCs [45,[72][73][74] as well as elevated arginase [75,76], dampening immunity in breast cancer through suppressive actions on CTLs, DCs and NK cells [76,77]. Metabolic enzymes such as indoleamine 2,3-dioxygenase (IDO), which is expressed by tumour cells and MDSCs, can also inhibit immune responses though local depletion of amino acids which are essential for anabolic functions, particularly in T lymphocytes [78,79].…”
Section: Mechanisms Of Immunity Generation and Suppression In Breast mentioning
confidence: 97%
“…The PDX model, which is established by transferring of primary tumors directly from the patient into an immunodeficient mouse, can retain the heterogeneity of primary tumor samples and more closely resembles the original clinical cancer than long-established cell lines and standard xenografts; thus, this model has emerged as a powerful tool for studying tumor xenografts [32] . Most CAR-NK cells are transferred to the PDX model to evaluate their safety and efficacy in pre-clinical trials, including CAR-targeting antigens from hematological cancers (eg, CD19, CD20, CD138, and CS-1) [33][34][35][36][37][38] and solid tumors (eg, HER2, EpCam, GD2, GPA7, PSCA, EGFR and EGFRvIII) [14,26,[39][40][41][42][43][44][45][46] (Table 1).…”
Section: Current Progress In the Use Of Car-nk Cells From Investigatmentioning
confidence: 99%
“…In a study by Liu et al, the plasmid coding anti-HER2-CD28-CD3ζCAR was transfected into NK-92 cells by electroporation, and the cells specifically killed the ErbB2-expressing human breast cancer cell lines MDA-MB-453 and SKBr3. The adoptive transfer of NK-92 cells specifically reduced the tumor size and lung metastasis of nude mice transplanted with MDA-MB-453 cells and significantly prolonged the survival of these mice [176]. Table 3, CAR against various tumor-associated antigens (TAA) has also been evaluated in NK cells.…”
Section: Improvement Of Tumor-specific Cytotoxic Activitymentioning
confidence: 99%